Weakened Aerosol‐PBL Interaction During COVID‐19 Lockdown in Northern China. Issue 3 (2nd February 2021) - Wang, Zilin; Huang, Xin; Ding, Ke; Ren, Chuanhua; Cao, Lu; Zhou, Derong; Gao, Jian; Ding, Aijun
Abstract: Anthropogenic emissions were greatly constrained during COVID‐19 lockdown in China. Nevertheless, observations still showed high loadings of fine particles (PM2.5 ) over northern China with secondary aerosols increasing by 15 μg/m 3 yet a ∼10% drop in light‐absorbing black carbon (BC). Such a chemical transition in aerosol composition tended to make the atmosphere more scattering, indicated by satellite‐retrieved aerosol absorption optical depth falling by 60%. Comparison between weather forecast and radiosonde observations illustrated that, without upper‐level heating induced by BC, the stabilized stratification diminished, which was conducive for planetary boundary layer (PBL) mixing and thus near‐surface pollution dispersion. Furthermore, coupled dynamic‐chemistry simulations estimated that emission reduction during the lockdown weakened aerosol‐PBL interaction and thus a reduction of 25 μg/m 3 (∼50%) in PM2.5 enhancement. Based on the unique natural experiment, this work observationally confirmed and numerically quantified the importance of BC‐induced meteorological feedback, further highlighting the priority of BC control in haze mitigation. Plain Language Summary: Atmospheric scattering and absorbing aerosols can both reduce sunlight reaching the earth surface, resulting in a surface cooling. Absorbing aerosols can also warm the upper air by trapping solar energy in the atmosphere. Such an opposite‐changing temperature tendency in these two levels leads to a stable air mass, which is conducive for pollutant accumulation and air quality deterioration. Due to the emission reduction during COVID‐19 lockdown, secondary scattering aerosols increased yet absorbing aerosols from primary emission decreased, accompanied with less stable air masses in the lower atmosphere. The reduced stability indicates that absorbing aerosols play a dominant role in suppressing boundary layer development and aggravating near‐surface pollution accumulation. Thus, further efforts devoted to emission reduction of absorbing aerosols like black carbon may serve as an efficient approach for pollution mitigation. Key Points: Heavy haze still engulfed northern China despite great emission reductions during COVID‐19 lockdown Enhanced secondary aerosols and decreased black carbon (BC) led to a more scattering atmosphere and weakened aerosol‐planetary boundary layer interaction Observational evidences and quantitative modeling confirmed the importance of BC during the unique natural experiment